A SECURITY ARCHITECTURE FOR SOFTWARE DEFINED NETWORK (SDN) - Adekunle, Okunade Oluwasogo; Oluwaseyi, Osunade (FUDMA Journal of Sciences, 2023)
Software defined network is emerging network architecture with promising future in network field. It is dynamic, manageable, cost effective, and adaptable networking where control and data plane are decoupled, and control plane is centrally located to control application and data planes. OpenFlow is an example of Software Defined Network (SDN) Southbound, which provides an open standard based interface between the SDN controller and data planes to control how datapackets are forwarded through the network. As a result of rapid changes in networking, SDN program-ability and control logic centralization capabilities introduces new fault and easily attack planes, that open doors for threats that where not exist or harder to exploit. The paper present SDN architecture with security control level, this provide secured SDN paradigm with machine learning white/black list, where users application can be easily tested and group accordingly (malicious attack or legitimate packet).
Keywords: Software Defined Network (SDN), OpenFlow, Flow Table, Security Control, White/Black List